ANALISIS JUSTIFIKASI LARANGAN EKSPOR BIJIH NIKEL INDONESIA DALAM PERSPEKTIF HUKUM PERDAGANGAN INTERNASIONAL - Clarissa Holil (CV Rewang Rencang, 2024)
Indonesia's nickel ore export ban through the Minister of Energy and Mineral Resources Regulation No. 11 of 2019 prompted European Union to bring the case to the WTO Panel, which concluded that Indonesia has violated Article 11 of the General Agreement on Tariffs and Trade (GATT). Using normative juridical research methods, this article examines Indonesia's justification for its export ban from the international trade law perspective. This study indicates Indonesia's uncertainty due to the dysfunctional WTO Appellate Body for an indefinite period, compelling Indonesia to consider a beneficial middle-ground approach for the economy while maintaining Indonesia's position in international trade.